Knowing, Doing and Being Pedagogy in MBA‐level Management Accounting Classes: Some Empirical Evidence. Issue 3 (September 2015) - Thaker, Keyur
<x xml:space="preserve">Abstract</x> Much of the educational literature is concerned with the value added by MBA programs. In particular, serious questions have been raised about the efficacy of curricula employed in MBA programs and the achievement of learning needs. These include appreciating organisational reality, offering hands‐on experience on effective implementation, assisting students to understand the limits of markets and models, integrating diverse issues, implementation, creativity and innovation, amongst others. This article argues for, and provides empirical support to, a pedagogy mix to complement prevalent case‐based methods in a compulsory MBA program management accounting course. The article discusses field visits and field‐based assignments, use of cases and role‐play in effectively addressing the knowing, doing and being learning needs within an MBA program. Student survey data provide empirical support to concerns in the literature about case‐based pedagogy, and supports the argument for a pedagogy mix.